96.3k views
3 votes
See attachment below

See attachment below-example-1
User Namaskar
by
4.6k points

1 Answer

5 votes

Answer: Third Option


x=1.469743

Explanation:

We have the following exponential equation


3^(x+1)=15

We must solve the equation for the variable x

To clear the variable x apply the
log_3 function on both sides of the equation


log_3(3^(x+1))=log_3(15)

Simplifying we get the following:


x+1=log_3(15)

To simplify the expression
log_3 (15) we apply the base change property


log_b(y)=(log(y))/(log(b))

This means that:


log_3 (15)=(log(15))/(log(3))

Then:


x+1=(log(15))/(log(3))


x=(log(15))/(log(3))-1


x=1.469743

User Quodlibetor
by
5.3k points